Examining the Efficacy of Targeted Component Interventions on Language and Literacy for Third and Fourth Graders Who are at Risk of Comprehension Difficulties. (2nd November 2018) - Connor, Carol McDonald; Phillips, Beth M.; Kim, Young–Suk Grace; Lonigan, Christopher J.; Kaschak, Michael P.; Crowe, Elizabeth; Dombek, Jennifer; Al Otaiba, Stephanie
ABSTRACT: Testing a component model of reading comprehension in a randomized controlled trial, we evaluated the efficacy of 4 interventions that were designed to target components of language and metacognition that predict children's reading comprehension: vocabulary, listening comprehension, comprehension of literate language, academic knowledge, and comprehension monitoring. Third- and 4th-graders with language skills falling below age expectations participated ( N  = 645). Overall, the component interventions were only somewhat effective in improving the targeted skills, compared to a business-as-usual control ( g ranged from −.14 to .33), and no main effects were significant after correcting for multiple comparisons. Effects did not generalize to other language skills or to students' reading comprehension. Moreover, there were Child Characteristic × Treatment interaction effects. For example, the intervention designed to build sensorimotor mental representations was more effective for children with weaker vocabulary skills. Implications for component models of reading and interventions for children at risk of reading comprehension difficulties are discussed.